The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.18203/2394-6040.ijcmph20163929
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological correlates of tobacco consumption among women in reproductive age group- a community based cross sectional study in the rural area of Belgaum District, Karnataka, South India

Abstract: INTRODUCTION "Tobacco" appears as old as human civilization. Tobacco use is world's number one killer and it kills up to half of its regular users. It is claiming the lives of nearly 5.4 million people a year worldwide. 1 Burden in South East Asia region is one of the highest among WHO regions. Estimated number of tobacco users in India is 274.9 million with a lot of regional variation. 2 In India, each year nine lakh people die due to tobacco related diseases ABSTRACT Background: Tobacco kills both men and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Participants from poor households had higher risks of tobacco use. This aligns with past studies conducted in India [ 66 ] and Iran [ 67 ] while this result is in contrast to the study by Kulkarni et al in southern India [ 68 ]. People struggling with adverse conditions are generally affected physically and psychologically, and are also vulnerable to natural and unnatural stresses [ 69 ].…”
Section: Discussionsupporting
confidence: 90%
“…Participants from poor households had higher risks of tobacco use. This aligns with past studies conducted in India [ 66 ] and Iran [ 67 ] while this result is in contrast to the study by Kulkarni et al in southern India [ 68 ]. People struggling with adverse conditions are generally affected physically and psychologically, and are also vulnerable to natural and unnatural stresses [ 69 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the study of socioeconomic classes in the county level, the results of the analysis showed that those in higher economic classes were less likely to use tobacco than those in lower economic classes, so that people in the fifth quintile were less likely to smoke than those in the first quantile, as 26% (1-e-0.3) (Table 4). The prevalence of tobacco smoking as a major public health problem has been widespread in Iran and in the world [9] . Today, in most high-income countries, there is a negative trend in tobacco use, so smoking is more common in people with a lower socioeconomic status.…”
Section: Total Country 31mentioning
confidence: 99%
“…[39] The study by Bosdriesz et al showed that in Latin America and the Eastern Mediterranean countries, the prevalence of tobacco smoking among women in higher socio-economic classes was higher, which did not match the results of our study in Iran. [9] In lower socioeconomic classes, tobacco smoking costs replaces other essential health costs, which in the long run lead to serious complications, the incidence of illness and death due to the use of tobacco, and consequently enlarges the gap between economic and social inequalities. [43] The results of Badr's study in multilevel analysis showed that educational level does not cause socioeconomic inequality in smoking, while in the urban areas, the results of the multilevel analysis revealed that the chances of smoking in people with a high school education was higher than the illiterates.…”
Section: Total Country 31mentioning
confidence: 99%
See 1 more Smart Citation